Sports motivation and goal orientation of young Serbian basketball players - Mladenovic, M.; Trunic, N. (Sport Science & Practice, 2015)
For optimal psychological development and affirmation of young athletes, it is important to highlight instrinsic motives and goal orientations aimed at managing the tasks and development of competencies. The aim of this research was to study sports motivation and goal orientation of young basketball players of U16 Serbian national team. 21 basketball players have been examined, aged 15-16. Sport motivation scale (SMS-28) and goal orientation scale (TEOSQ) have been used. The values of Cronbach alpha show satisfying validity of these instruments. The data have been analyzed by descriptive statistics and correlation analysis. The results have shown that instrinsic motives and goal orientation are primarily directed towards development of competencies